Peran Kepemimpinan Transformasional dalam Memperkuat Pengaruh Efikasi diri dan Motivasi pada Kinerja Pegawai - Triatiana Rijanti; Kis Indriyaningrum; Askar Yunianto; Ibrahim Yusuf (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2020)
This study aims to examine the role of transformational leadership in strengthening efikasi diri and motivation effect on employee performance. The population of this study were employees while the sampling technique was used simple random sampling. Using Slovin formula, found 100 respondents. Data were collected by questionnaires and analyzed using SPSS by testing the instrument, model and hypothesis. This research uesed a multiple linier regression analysis. Based on the results of hyphotesis testing shows that self efficacy and motivation have positive and significant effect on performance, and transformational leadership moderates the both offect of self efficacy and motivation on performance.